Letter : Shoes for Spain - Schevenels, Walther, b. 1894
030-0097-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe IFTU Sch/H TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter F. I. de Sol No. 708 8th August 1938. Mr. H.V. Tewson, London. Dear Comrade Tewson, SHOES FOR SPAIN I duly received your letter of the 4th instant, regarding shoes for Spain and I have already informed Santiago accordingly. As soon as you let us have precise information as to the despatch, we will let him know the date of arrival of the consignment. Yours sincerely, W. Schevenels, General Secretary: 292/946/30/97